Performance nutrition : applying the science of nutrient timing - Austin, Krista, 1977-; Seebohar, Bob (Champaign, IL : Human Kinetics)
Blends theory with applied content and real-life examples to help nutritionists, coaches, and athletes design nutrition plans based on each athlete's individual needs and the specific demands of the sport.